Broadcasting and development in a multicultural society: community broadcasting policy in a post-apartheid South Africa. - Keene-Young, Bronwyn Elaine. (My University, 1994)
Community broadcasting in South Africa has been identified as an ideal medium for the facilitation of participatory communiry development. The objectives of community ownership and participation in community broadcasting are perceived as the basis for the empowerment of people who were oppressed by apartheid. The establishment of the Independent Broadcasting Authority (lBA) in 1994 has provided the framework for the development of a community broadcasting sector. However, the interpretation of the IRA Act, and the general policy which is adopted towards community broadcasting will determine the longterm sustainabilitv of the sector in South Africa. It will also determine the extent to which community broadcasting achieves the ideals of local development and empowerment. This dissertation addresses both the objectives for the use of community broadcasting in development, and the policies which are required for the development of the community broadcasting sector.
A Dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Master of Arts.
Keywords: Broadcasting -- South Africa.; Community development -- South Africa.